Kegiatan Bersih-Bersih Makam Umum dalam Rangka Menyambut Haul Bujuk Sorat di Desa Balunganyar - Achmad Nur Rofiuddin; Prafita Fardhany Aslam; Dewi Qurrota Ayun; Wakid Evendi; Muhammad Zakki; Arif Rachman Putra; Samsul Arifin; Muchamad Catur Rizky; Adi Herisasono; Solchan Ghozali (Universitas 45 Surabaya, 2025)
The public grave cleaning activity in Balunganyar Village was carried out to welcome Haul Bujuk Sorat, aiming to improve the cleanliness, comfort and tidiness of the grave area. Through the PAR method, this activity involves various elements of society with a method that includes initial preparation stages, division of tasks, implementation, rest and consumption, closing, as well as reporting and documentation. The results of the activity showed that effective coordination between the committee, community leaders and participants supported the smooth running of all stages. Active community participation reflects strong support for this program, which has a positive impact on the cleanliness and tidiness of graves, as well as strengthening social and religious values ​​in the community. The resulting long-term impacts include increasing a sense of togetherness, awareness of the importance of environmental cleanliness, and preserving local traditions. Evaluation of the activity showed high community enthusiasm, with suggestions that this activity be held regularly for the sake of sustainable benefits for Balunganyar Village.